ANALISIS KINERJA KONTEKSTUAL KARYAWAN PADA PT AEROJASA CARGO JAKARTA - Erni Pratiwi Perwitasari (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
Empowerment is rising employee potential and increasing their motivation so that they willbe more adaptive. Employee empowerment is the key to create employee’s power that motivated sothat they are working properly and excitedly with their vision. An outcome work that reached by aperson in performing his or her duties of work achievement, responsibility , obedience , honesty ,cooperation and initiatives is called performance. Performance is formed by an employee motivationand performance can be final result, in a form of behavior, skill, competence, facilities and specificskill that can support the achievement of a goal organization.This research was done on employee of PT. Aerojasa Cargo Jakarta. The result of thisresearch concluded that employee empowerment and motivation have positive reciprocal influenceboth partial and simultaneous on contextual performance.